A new benzofuran derivative from the leaves of Ficus pumila L. Issue 14 (18th July 2018) - Trinh, Pham Thi Nhat; An, Nguyen Huu; An, Pham Ngoc; Tri, Mai Dinh; Du, Cao Van; Minh, Phan Nhat; Thuy, Nguyen Thi Le; Tuan, Nguyen Trong; Thoa, Vang Thi Kim; Tuan, Nguyen Ngoc; Dung, Le Tien
Abstract: A new benzofuran derivative, pumiloside (1 ), together with seven known flavonoid glycosides, afzelin (2 ), astragalin (3 ), quercitrin (4 ), isoquercitrin (5 ), kaempferol 3- O -rutinoside (6 ), rutin (7 ) and kaempferol 3- O -sophoroside (8 ) were isolated from the leaves of Ficus pumila . Their structures were established by spectroscopic data and comparison with the literature values. Abstract :